Drug-Related Problems and Pharmacist Interventions in Paediatric In-Patients at a Tertiary Care Teaching Hospital: A Prospective Observational Study - Hegde, Raghavendra Shivaram; Sowmya, Sowmya; Sree, Ramya; Rathod, Ajeet Singh; Shalavadi, Mallappa; Keshannavar, Mudakappa (Indian Journal of Pharmacy Practice, 2026)
Background: Paediatric in-patients are particularly vulnerable to Drug-Related Problems (DRPs) owing to physiological immaturity, weight-based dosing, and widespread off-label medicine use. Objectives: To identify and categorise DRPs, evaluate prescribing patterns and rationality against standard guidelines, assess pharmacist intervention outcomes, and perform a cost analysis of drug therapy in paediatric in-patients at a tertiary care teaching hospital. Materials and Methods: A six-month prospective observational study was conducted in the PICU, NICU, and General Paediatric wards of a tertiary care teaching hospital. A total of 135 in-patients aged 18 years or younger were enrolled. Prescriptions were reviewed daily; DRPs were classified using the Strand classification; rationality was assessed against Indian Academy of Paediatrics (IAP) recommendations. The chi-square test was applied, with significance set at p<0.05. Results: Of 135 patients, lower respiratory tract infection was the most frequent diagnosis (25.9%). Overall, 71.85% of prescriptions were rational and 28.15% irrational. A total of 139 DRPs were identified, predominantly drug-drug interactions (38.1%) and adverse drug reactions (20.9%). Polypharmacy occurred in 84.4% of patients and accounted for 79.1% of DRPs. Of 139 pharmacist suggestions, 46.8% were accepted by physicians, resulting in a change of therapy in 36.0% of cases. Conclusion: The high burden of DRPs and irrational prescribing supports routine clinical pharmacist participation in paediatric care. Physician receptiveness to suggestions demonstrates the clinical relevance of these services.
Keywords: Clinical Pharmacy Services; Drug-Related Problems; Paediatrics; Polypharmacy; Prescription Rationality